Informed participation? An investigation of the relationship between exposure to different news channels and participation mediated through actual and perceived knowledge - Schäfer, Svenja; Schemer, Christian (Frontiers in Psychology, 2024)
Previous studies have found that different media channels have varying potentials for informed participation. Exposure to newspaper and TV news exposure has been shown to increase actual knowledge and participation, while social media is associated with participation based on perceived knowledge, without changes in actual knowledge. In light of these findings, we conducted an online survey (N = 1,670) in Germany to investigate the (mediated) relationships between news consumption, knowledge (perception), and participation. The study revealed that exposure to quality newspaper and public service TV news was linked to both actual and perceived knowledge, thereby impacting participation. However, tabloid newspapers and news from private TV channels were not found to be related to participation. In the case of social media, we found a relationship with online participation on social media and offline participation, but this relationship was only mediated through an increase in perceived knowledge. In other words, our findings suggest that social media use creates an illusion of knowledge that is linked to higher levels of participation. These findings highlight the democratic importance of traditional media channels, particularly public service broadcasting media. They also demonstrate how social media can lead to a false feeling of knowing, which can hinder participation processes.